Dopamine-Dependent QR2 Pathway Activation in CA1 Interneurons Enhances Novel Memory Formation - Gould, Nathaniel L. (J Neurosci, 2020)
The formation of memory for a novel experience is a critical cognitive capacity. The ability to form novel memories is sensitive to age-related pathologies and disease, to which prolonged metabolic stress is a major contributing factor. Presently, we describe a dopamine-dependent redox modulation pathway within the hippocampus of male mice that promotes memory consolidation. Namely, following novel information acquisition, quinone reductase 2 (QR2) is suppressed by miRNA-182 (miR-182) in the CA1 region of the hippocampus via dopamine D1 receptor (D1R) activation, a process largely facilitated by locus coeruleus activity. This pathway activation reduces ROS generated by QR2 enzymatic activity, a process that alters the intrinsic properties of CA1 interneurons 3 h following learning, in a form of oxidative eustress. Interestingly, novel experience decreases QR2 expression predominately in inhibitory interneurons. Additionally, we find that in aged animals this newly described QR2 pathway is chronically under activated, resulting in miR-182 underexpression and QR2 overexpression. This leads to accumulative oxidative stress, which can be seen in CA1 via increased levels of oxidized, inactivated potassium channel Kv2.1, which undergoes disulfide bridge oligomerization. This newly described interneuron-specific molecular pathway lies alongside the known mRNA translation-dependent processes necessary for long-term memory formation, entrained by dopamine in CA1. It is a process crucial for the distinguishing features of novel memory, and points to a promising new target for memory enhancement in aging and age-dependent diseases. SIGNIFICANCE STATEMENT One way in which evolution dictates which sensory information will stabilize as an internal representation, relies on information novelty. Dopamine is a central neuromodulator involved in this process in the mammalian hippocampus. Here, we describe for the first time a dopamine D1 receptor-dependent quinone reductase 2 pathway in interneurons. This is a targeted redox event necessary to delineate a novel experience to a robust long-term internal representation. Activation of this pathway alone can explain the effect novelty has on “flashbulb” memories, and it can become dysfunctional with age and diseases, such as Alzheimer's disease.